(untitled) (EAAE Annual Conference Proceedings, 2023)
During the educational process of architecture, the studio space generously hosts both living and non-living constituents, including students, instructors/lecturers, invited individuals, digital or physical agents, owned/hacked/open-sourced components and strategies, online or offline tools, and more.